The influence of rehabilitation on the functional status and pain in patients with spinal overload syndrome - Czenczek-Lewandowska, Ewelina; Przysada, Grzegorz; Brotoń, Karolina; Leszczak, Justyna; Rykała, Justyna; Podgórska-Bednarz, Justyna (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Lumbosacral pain is becoming an increasing social problem due to its prevalence and is currently believed to be a lifestyle disease. Its occurrence is most frequently affected by accumulating spinal overload which may be related inter alia to work, environment and lifestyle. Aim: The aim of this study was to evaluate the effect of rehabilitation on the functional status and perception of pain in patients with diagnosed lumbosacral overload syndrome. The analysis took into consideration the living environment and the kind of work. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: The study included 50 people with advanced lumbosacral pain, who lived in rural areas and in course of their treatment attended rehabilitation. The respondents were both white and blue collar workers. Degree of disability and pain sensations were determined with the Oswestry questionnaire and the Laitinen scale. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: Rehabilitation had a positive impact on improving the functional status and alleviated pain sensation in people with lumbosacral overload syndrome. It has been observed that in spite of beneficial effects of treatment, people working physically achieved worse results both before and after rehabilitation compared to white-collar workers. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The physical character of work is an important factor in developing lower back overload and pain.